Tataniaga Jeruk Siam (Citrus Nobilis Lour) di Desa Sungai Kambat Kecamatan Cerbon Kabupaten Barito Kuala - Sri Astuty Handayani; Abdullah Dja'far; Ahmad Yousuf Kurniawan (Universitas Lambung Mangkurat, 2011)
The objectives of this research are: (1) to observe marketing channels, functions and marketing institution who involved in siam orange distribution, (2) to analize marketing costs, marketing shares, marketing margin, profit and marketing efficiency feasibility of siam orange marketing, and (3) to identify siam orange marketing problems in its channels. In this research, data were collected by interviewing 30 farmers from 3 different farmer groups. Then, by snowball sampling technique with those farmers as the starting point, 2 colector traders, 2 whole salers, and 2 retails also were interviewed. The results revealed that Sungai Kambat Village have five marketing channels. As the dominant channel, the third channel has the highest score in economic and technical efficiency. The marketing costs consist of transportation, loading and dropping, fees and taxes, and fruit damage. The higher marketing cost was occured in the second channel while the lowest one was in the first channels. Marketing shares and margins were varied depend on cost, fruit sales, and fruit’s retail price. Siam orange marketing in all channels were economicly feasible. And finally, the most common problems in this marketing were uncertainty price, fruit quality, and illegal fees.